Healthcare associated infections in gynecologic oncology: clinical and economic impact. Issue 2 (29th December 2022) - Biscione, Antonella; Corrado, Giacomo; Quagliozzi, Lorena; Federico, Alex; Franco, Rita; Franza, Laura; Tamburrini, Enrica; Spanu, Teresa; Scambia, Giovanni; Fagotti, Anna
Abstract : Objective: The purpose of this study was to assess the rate and type of infections in gynecological cancer patients. We also performed an economic analysis to provide an overview of costs related to healthcare associated infections. Methods: We retrospectively collected data from culture samples at the site of infection from patients undergoing surgery or chemotherapy, admitted to the Gynecologic Oncology Unit, Fondazione Policlinico Agostino Gemelli IRCCS, from January 2017 to December 2018. We performed univariate and multivariate analyses to calculate potential risk factors for prolonged length of hospitalization. The average cost per patient was calculated, including the cost of hospital stay, operating room, medications, and diagnostic and invasive procedures. Results: Among 5682 patients, 322 (5.6%) gynecological cancer patients with healthcare associated infections were identified. A total of 249 patients (77.3%) had undergone surgery in the previous 30 days and 73 (22.7%) patients were receiving chemotherapy. In the whole population, the most common healthcare associated infections were urinary infections (58%) and surgical wound infections (42.1%). In addition, 14.5% of patients had central venous catheter infections and 21.7% had blood stream infections. Median length of stay was 20 days (range 1–100). Among surgical patients, advanced age (odds ratio (OR) 1.233, 95% confidence interval (CI) 1.001 to 1.519, p=0.049), bowel resection (OR 2.659, 95% CI 1.493 to 4.735, p=0.001), surgical site infection (OR 10.447, 95% CI 1.143 to 95.5, p=0.038), and central venous catheter infection (OR 9.856, 95% CI 1.139 to 85.319, p=0.038) were independently associated with an increased risk of prolonged hospital stay (>20 days). The overall direct cost of healthcare associated infections was 6 273 852 per year. Conclusions: The infection rate in our population was 5.6%. The most common healthcare associated infections were urinary and surgical wound infections. Among surgical patients, advanced age, bowel resection, surgical site, and central venous catheter infection were associated with an increased length of hospitalization. Healthcare associated infections cause an increase in the length of stay after surgery and hospital costs.